Light of Mercury, or about a reformative role of the literary agent in development of book business of Kazakhstan (Herald of Journalism, 2016)
Proceeding from forecasts of economists that «the forthcoming 15-17 years will become «window of opportunities» for large-scale break of Kazakhstan» and providing various economic theories (R. Kantilyon,I. Tyunen and F. Knight, authors of article put forward idea that the literary agent whom already private and state publishing houses and offtakers of a book product now need will become the intellectual and innovative engine of book business during this period. If in the conditions of the accruing competition moving publishing (the economic – Y. Shumpeter) system to consider all in the mode of real dynamics if the initiative of the businessman is a key source of selfdevelopmentof economy, the literary agent is the most important tool of its innovation: an irreplaceable source of self-development of economy of book firm (P. Druker, B. Karloff and B. Santo) and a key figure of the realization and profit, means of attraction of investments focusing firm on success.For the book businessman the literary agent acts not only a potential source of the income, but also the advertizing agent, the instrument of selection of socially useful values and formations of the intellectualperson of society. In some cases the literary agent becomes a key figure on which both growth, and quality of sales in many respects depends.
Keywords: literary agent; book business; monitoring; innovation; innovative and intellectual management; publishing; polygraphy; author; consumer; competitor; competitive environment